Melting and Refreezing in an Ice Shelf Basal Channel at the Grounding Line of the Kamb Ice Stream, West Antarctica. Issue 11 (24th November 2022) - Whiteford, A.; Horgan, H. J.; Leong, W. J.; Forbes, M.
Abstract: Ice shelves buttress ice streams and glaciers, slowing the rate at which they flow into the ocean. When this buttressing is reduced, either through increased melt or calving, the increased discharge of grounded ice upstream contributes to sea level rise. The thickness, strength, and stability of ice shelves can be influenced by channels in the ice base. Here, we focus on a subglacially sourced basal channel which is observed to have melted up to 50% of the ice shelf thickness. The channel extends 6 km upstream of the previously estimated grounding line of the stagnant Kamb Ice Stream. Using a combination of ground–based observations and remote sensing, we find that the channel is growing upstream over time. Over–snow radar surveying images the shape of the channel, constrains a steep inception, and shows that not all of the basal shape is manifest at the surface. Modern surface lowering at the upstream head of the channel is interpreted as a region of focused melt where a subglacial outlet meets the ocean cavity. We estimate this basal melt to be at least 35 m/a in a narrow (200 m × 1.5 km) zone. Downstream from the melt region, repeat phase sensitive radar observations reveal accretion contributing to the growth of a ledge on the true–right side of the channel. We conclude that the channel is likely formed by a retreating subglacial outlet which enhances basal melt episodically. Plain Language Summary: Ice flows off the Antarctic continent and floats on the surrounding ocean, forming ice shelves. These ice shelves get stuck against the Antarctic coastline and islands, blocking ice flow from the continent to the open ocean. When ice shelves break apart or thin by melting, they have less ability to block ice flow. As a result, more ice flows from the continent into the ocean resulting in sea level rise. Melting can be especially strong in channels which form underneath floating ice. This paper focuses on a channel melted into the base of the Ross Ice Shelf at the inland coastline. We used radar to map the channel and found that it has a similar shape to a river mouth, though under approximately 350 m of ice. Water from the Antarctic continent flows to the ocean through this channel. Using data from satellites we found an area on the ice surface above the channel which is lowering, likely because of melting in the channel underneath. We estimated that the ice base is melting by at least 35 m per year in a narrow zone. Downstream, we used radar to find that in the channel water is freezing to the base of the ice shelf. Key Points: Oversnow radar data reveals the shape of a subglacially sourced basal channel at the grounding line of the Kamb Ice Stream Remote sensing suggests that more than 35 m/a melt occurs at the upstream tip of the channel, and shows that the channel is growing upstream Repeat autonomous phase‐sensitive radio‐echo sounder surveying shows accretion across the channel downstream from the channels inception